2008
DOI: 10.1007/s10571-008-9313-y
|View full text |Cite
|
Sign up to set email alerts
|

l-Carnitine Blood Levels and Oxidative Stress in Treated Phenylketonuric Patients

Abstract: Our results suggest that L-carnitine should be measured in plasma of treated PKU patients, and when a decrease of this endogenous component is detected in plasma, supplementation should be considered as an adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 31 publications
0
39
0
1
Order By: Relevance
“…The investigation of redox status in cell cultures exposed to the metabolites and in the liver-specific HL-deficient mice model developed by Gauthier et al (2013) would also be of great importance for this purpose. As regards to L-carnitine, it was shown that supplementation of this compound normalized various parameters of oxidative stress in patients with HL deficiency and other inborn errors (Sitta et al 2009;Mescka et al 2013;dos Santos et al 2015;Guerreiro et al 2015). This beneficial effect could be due to its capacity to remove toxic metabolites and/or its antioxidant properties, signalizing the potential use of this compound as an adjuvant therapy for these inherited metabolic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of redox status in cell cultures exposed to the metabolites and in the liver-specific HL-deficient mice model developed by Gauthier et al (2013) would also be of great importance for this purpose. As regards to L-carnitine, it was shown that supplementation of this compound normalized various parameters of oxidative stress in patients with HL deficiency and other inborn errors (Sitta et al 2009;Mescka et al 2013;dos Santos et al 2015;Guerreiro et al 2015). This beneficial effect could be due to its capacity to remove toxic metabolites and/or its antioxidant properties, signalizing the potential use of this compound as an adjuvant therapy for these inherited metabolic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…An increase of malondialdehyde, which is a marker of lipid peroxidation, was observed in plasma of PKU patients at diagnosis and during dietary treatment (Colomé et al 2003;Gassió et al 2008;Sitta et al 2006Sitta et al , 2009bSirtori et al 2005). In addition, increased lipid and protein oxidative damage was also verified in plasma from affected patients with late diagnosis as compared to early diagnosed PKU patients (Sitta et al 2009c).…”
Section: Oxidative Stress In Pku Patientsmentioning
confidence: 99%
“…When the disorder is diagnosed and treated promptly at an early age, mental retardation can be prevented, although mild neuropsychological findings, such as poor school performance and a slight reduction in the intelligence quotient may occur, especially when careful dietary compliance is not achieved (Weglage et al 1995). However, deficiency of selenium and carnitine has been found in treated PKU patients, probably secondary to a poor dietary compliance with the enriched formulas or impaired bioavailability of some micronutrients in these diets (Acosta et al 1999;van Bakel et al 2000;Gassió et al 2008;Sitta et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, DNA damage was reported in peripheral blood from PKU patients in vivo and in vitro in a dosedependent manner [31,32]. In addition, protein and lipid oxidative damage, measured by carbonyl formation and sulfhydryl oxidation, and thiobarbituric acid-reactive species (TBA-RS) and malondialdehyde (MDA) content, respectively, were described in plasma and erythrocytes from PKU patients [31,[33][34][35][36]. Decreased antioxidant defenses, both enzymatic and non-enzymatic, were also found in these subjects.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Decreased antioxidant defenses, both enzymatic and non-enzymatic, were also found in these subjects. Low levels of plasma total antioxidant status and reactivity, L-carnitine, betacarotene and coenzyme Q10, and altered catalase [CAT], superoxide dismutase [SOD] and glutathione peroxidase [GPx] activities in PKU patients samples indicate an impairment of antioxidant defense that could result in oxidative stress [31,33,35,36]. Some of these findings were reversed by L-carnitine and selenium supplementation [37].…”
Section: Oxidative Stressmentioning
confidence: 99%